2019
DOI: 10.3390/cli7110132
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Climate Change Adaptation in Sub-Saharan Africa: A Review of Climate-Smart Agriculture among Small-Scale Farmers

Abstract: Climate-smart agriculture (CSA) as a credible alternative to tackle food insecurity under the changing climate is gaining wide acceptance. However, many developing countries have realized that concepts that have been recommended as solutions to existing problems are not suitable in their contexts. This paper synthesizes a subset of literature on CSA in the context of small-scale agriculture in sub-Saharan Africa as it relates to the need for CSA, factors influencing CSA adoption, and the challenges involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 86 publications
3
68
0
Order By: Relevance
“…For instance, Thornton et al, 2009 andOmoyo et al, 2015 had demonstrated that crop yields in Africa at lower altitudes is likely to fall by 20-50 % because of drying and warming as a result of climate change. Furthermore, most recent climate predictions of future green house gas-induced climate change clearly suggest that this warming will continue rising under most scenarios such that in Africa up to the end of the century (Abegunde et al,2019) From our study its accelerating up to 0.03 o C implying in 100 years it would be 3.0 o C within the range suggested by Hulme et al, (2001). The high temperatures in lower highlands in Kenya will most likely increase evaporation, soil moisture and heat stress and worsen household food insecurity, hamper poverty reduction efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Thornton et al, 2009 andOmoyo et al, 2015 had demonstrated that crop yields in Africa at lower altitudes is likely to fall by 20-50 % because of drying and warming as a result of climate change. Furthermore, most recent climate predictions of future green house gas-induced climate change clearly suggest that this warming will continue rising under most scenarios such that in Africa up to the end of the century (Abegunde et al,2019) From our study its accelerating up to 0.03 o C implying in 100 years it would be 3.0 o C within the range suggested by Hulme et al, (2001). The high temperatures in lower highlands in Kenya will most likely increase evaporation, soil moisture and heat stress and worsen household food insecurity, hamper poverty reduction efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Climate variability and change is another factor undermining the performance of the crop thus putting into risk the food and economic security of the small scale farmers (Ogeto et al, 2013;Abegunde, et al, 2019). Extreme weather and climate events such as drought in the Arid and Semi-Arid Lands (ASALs) has been increasing in frequency and intensity making sorghum cereal a preferred crop than maize for household food security (Omoyo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overwhelming majority of hungry people are found in developing countries, particularly in Africa (Abegunde et al 2019). With increasing recognition of present and future impacts of climate change, the United Nations Framework Convention on Climate Change (UNFCC 2006) has identified the poorest people living in developing countries as the most vulnerable due to their dependence on natural resources and rain-fed agriculture for survival.…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of smallholder farmers is a concern because they represent 85% of the world's farmers and provide more than 80% of the food consumed in the developing world; therefore, what happens to smallholder farmers will have significant social, economic, and environmental consequences globally (Vignola et al 2015). By their sheer numbers and with optimal productivity, they would have a huge impact in addressing food insecurity (Abegunde et al 2019), but because of low resource capacity, inadequate skills, and lack of enabling policies, they remain susceptible particularly to climate variability in Africa. Climate change adaptation has become necessary to alleviate the impacts of extreme weather events, especially on rural farmers whose primary livelihood is climate dependent (Cobbinah and Anane 2016).…”
Section: Introductionmentioning
confidence: 99%